(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
Testosterone is commonly used as a marker probe drug for CYP3A4 metabolic activity. Accurate measurement of its metabolite, 6β-hydroxytestosterone in cell culture media is very crucial. This study aimed to optimize solvent extraction method as well as to develop and validate HPLC analytical method for the quantification of 6β-hydroxytestosterone. Testosterone and 6β-hydroxytestost-erone were extracted from culture media using different solvents and were analyzed using BCA assay and HPLC. The separation was performed at 0.7 mL/min flow rate, using gradient elution of water:methanol for 38 minutes at 242 nm. Solvent extraction of cell culture media using methanol showed the highest crude extract recovery, yield recovery of compounds, and percentage recovery of compounds and peak areas. Thus, the methanol extraction method was applied to further validate 6β-hydroxytestosterone HPLC analytical method. The specificity of the metabolite peak was excellent without any interference. The linear range was 0.156-5.000 ppm. The precision and accuracy were within acceptable criteria of <15%. Samples were stable at 4 ºC chiller for up to 5 days, in autosampler for 24 hours, and in -20 ºC freezer for up to one month. The method was successfully developed and validated for the quantification of 6β-hydroxytestosterone in cell culture media.